Amniotic fluid neutrophil gelatinase-associated lipocalin and L-type fatty acid-binding protein levels in predicting long-term prognosis in fetal growth restriction and preterm birth: a preliminary study - Katsura, Daisuke; Tsuji, Shunichiro; Tokoro, Shinsuke; Inatomi, Ayako; Kita, Nobuyuki; Murakami, Takashi (Frontiers in Pediatrics, 2026)
IntroductionThe fetal intrauterine environment, including inflammation and fetal hypoxia, influences both short- and long-term prognoses. Urinary neutrophil gelatinase-associated lipocalin (NGAL) and L-type fatty acid-binding protein (L-FABP) levels are associated with inflammation and organ hypoperfusion, respectively. In this study, we evaluated the association between amniotic fluid NGAL and L-FABP levels measured at delivery and long-term outcomes.MethodsAdverse outcomes were defined as hearing loss, neurodevelopmental impairment, and cerebral palsy. Thirty-one singleton pregnancies were categorized into groups with (AD group, n = 10) and without (non-AD group, n = 21) adverse outcomes. Patient characteristics, clinical outcomes, and NGAL and L-FABP levels were compared between groups.ResultsSignificant differences in the prevalence of fetal blood flow abnormalities (p = 0.003) and gestational age at delivery (p = 0.004) were observed between groups. NGAL and L-FABP levels were significantly higher in the AD group than in the non-AD group (p = 0.015 and p = 0.001, respectively). The areas under the curve for NGAL and L-FABP were 0.771 (cut-off: 26,700 µg/gCr) and 0.848 (cut-off: 1,250 µg/gCr), respectively.DiscussionAmniotic fluid NGAL and L-FABP levels were associated with adverse long-term outcomes, providing preliminary, proof-of-concept evidence of their potential prognostic relevance. Further prospective studies with larger cohorts are needed to validate these findings and clarify their clinical applicability.